Product-service system and possibilities of its application in the field of alternative energy - V. N. Andreev; N. J. Jumadurdyyev (Управление)
The aim of this article is to study and justify the possibilities of using a product-service system in the field of alternative energy, as well as to develop business-models for introducing relevant innovative developments in the field of renewable energy sources to the world market. Thus, CO₂ emissions are reduced, and the demand for green energy is met. There are few studies in the literature linking the product-service system and renewable energy sources. The originality of this work lies in the correlation of these two concepts. The authors conducted a preliminary analysis of the energy market and developed three business models based on the product-service system applicable in the field of renewable energy: On-Grid, Off-Grid and Hybrid systems. The results of the study show that the proposed business-models are ideal in an environment where traditional electricity tariffs are high or there is no power grid, as well as when it is possible to be a prosumer (consumer and producer of electricity at the same time) at the legislative level. The favorable impact of the product-service system application to renewable energy sources on the environment is substantiated. Also, the purchase of renewable energy by consumers will not require an initial investment. These models consider the demographic, legal, and cultural characteristics of countries and communities. Companies operating with renewable energy can apply these business-models regardless of which country they operate in or what type of renewable energy they provide, which shows the importance of applying alternative business-models for the development of renewable energy.